Unveiling the Molecular Architecture of HBV Spherical Subviral Particles: Structure, Symmetry, and Lipid Dynamics - Sonal Garg; Alyssa Ochetto; Jianming Hu; Joseph Che-Yen Wang (Viruses)
Since the discovery of the Australia antigen, now known as the hepatitis B surface antigen (HBsAg), significant research has been conducted to elucidate its physical, chemical, structural, and functional properties. Subviral particles (SVPs) containing HBsAg are highly immunogenic, non-infectious entities that have not only revolutionized vaccine development but also provided critical insights into HBV immune evasion and viral assembly. Recent advances in cryo-electron microscopy (cryo-EM) have uncovered the heterogeneity and dynamic nature of spherical HBV SVPs, emphasizing the essential role of lipid–protein interactions in maintaining particle stability. In this review, recent progress in understanding the molecular architecture of HBV SVPs is consolidated, focusing on their symmetry, lipid organization, and disassembly–reassembly dynamics. High-resolution structural models reveal unique lipid arrangements that stabilize hydrophobic residues, preserve antigenicity, and contribute to SVP functionality. These findings highlight the significance of hydrophobic interactions and lipid–protein dynamics in HBV SVP assembly and stability, offering valuable perspectives for optimizing SVP-based vaccine platforms and therapeutic strategies.